THE INTERNALISASI BUDAYA KERJA BERBASIS KEARIFAN LOKAL PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN TAKALAR - A Rahmat Pakaya Idris; Dr Halim; Dr Lukman Samboteng (Jurnal Administrasi Negara, 2020)
Culture Internalization Work of Civil Servant it is very important to make improvements to change the attitudes and behavior of civil servants in order to achieve higher work productivity in the face of future challanges. The purpose of this study was to determine the Internalization of Work Culture Based on Local Wisdom of Civil Servants at the Ragional Secretariat of Takalar Regency. The approach used in this research is a qualitative research method. The informants who become the source of information were 15 people. The results showed that the Internalization of the Work Culture of Civil Servants at the Ragional Secretariat of Takalar Regency was good enough based on the results of interviews and observations of researchers while carrying out the research, while the Internalization of work culture value of akkareso tojeng-tojeng (professional), work culture value of assamaturu, sipammaling-malingi (synergy), work culture value of sipakatau, sipakainga' and sipakalabbiri' (work ethic), work culture value of siri' na pacce (integrity), and work culture value of toddopuli (innovative) at the Ragional Secretariat of Takalar Regency, it is already good based on the results of the researchers interviews with informants and the results of the researchers observations, although with some notes related to challanges that hinder the application of these work cultural values.